Acute respiratory distress syndrome: a life threatening associated complication of SARS-CoV-2 infection inducing COVID-19. Issue 17 (22nd November 2021) - Badraoui, Riadh; Alrashedi, Mousa M.; El-May, Michèle Véronique; Bardakci, Fevzi
Abstract: Acute Respiratory Distress Syndrome (ARDS) is a form of respiratory failure in human. The number of deaths caused by SARS-CoV-2 infection inducing this severe pneumonia (ARDS) is relatively high. In fact, COVID-19 might get worsen in ARDS and provoke respiratory failure. A better understood of ARDS key features and the pathophysiological injuries of the pulmonary parenchyma are linked to lessons learned from previous severe diseases associated previous coronaviruses outbreaks (especially SARS-CoV and MERS-CoV) and more the ongoing SARS-CoV-2. The ARDS mechanism includes a diffuse alveolar damage associated disruption of alveolar capillary membrane, pulmonary edema, damaged endothelium and increased permeability. A diffuse inflammation, with acute onset, on the lung tissue accompanied by release of biochemical signal and inflammatory mediators (TNFα, IL-1 and IL-6) leading to hypoxemia, low PaO2 /FiO2 ratio and the chest radiological expression of bilateral infiltrates in ARDS. The ongoing outbreak could lead to a better understood of ARDS pathophysiology and prognostic. An overview is also highlighted about the seven coronaviruses proved to infect human especially those having ability to cause severe disease SARS-CoV, MERS-CoV and SARS-CoV-2. In this review, we focused on the major pathological mechanisms leading to the ARDS development as a result of viral infection, severe COVID-19 worsening. Communicated by Ramaswamy H. Sarma